Kepastian Hukum Terhadap Pemegang Hak Milik Atas Tanah Atas Penerbitan Sertifikat Ganda - Ahzaza Fahrani; Benny Djaja; Maman Sudirman (UNES Law Review, 2023)
Certificate of land ownership regulated in the Undang-Undang Pokok Agraria (UUPA) is an ownership proof of the land right where it becomes powerful evidence. The increasement of necessity of a land is not followed by the increasement of the availability of land that can be utilized by the society, which causes many disputes related to the ownership or land right. One of many problems that arises is double certificate on a land. Double certificate on a land causing risks on the owner of land right where such phenomena caused by the maladministration to criminal action. Badan Pertanahan Nasional (BPN) as an institution established by the Government that holds the sole authority in national land should be responsible in the matters related to the land dispute, especially double certificate. Beside that, there is a necessity on the legal protection to be provided by the State for the owner of land right to protect the rights of the land owner. The research performed using juridical normative with legislation approach and conseptual approach. The results of the research will be presented in the form of an explanatory-analysis where the author explains the legal certainty for land ownership holders regarding the issuance of double certificates